The underestimated significance of conditioning in placebo hypoalgesia and nocebo hyperalgesia - Bräscher, Anne-Kathrin; Witthöft, Michael; Becker, Susanne (Pain research & management, 2018)
Placebo and nocebo effects are intriguing phenomena in pain perception with important implications for clinical research and practice because they can alleviate or increase pain. According to current theoretical accounts, these effects can be shaped by verbal suggestions, social observational learning, and classical conditioning and are necessarily mediated by explicit expectation. In this review, we focus on the contribution of conditioning in the induction of placebo hypoalgesia and nocebo hyperalgesia and present accumulating evidence that conditioning independent from explicit expectation can cause these effects. Especially studies using subliminal stimulus presentation and implicit conditioning (i.e., without contingency awareness) that bypass the development of explicit expectation suggest that conditioning without explicit expectation can lead to placebo and nocebo effects in pain perception. Because only few studies have investigated clinical samples, the picture seems less clear when it comes to patient populations with chronic pain. However, conditioning appears to be a promising means to optimize treatment. In order to get a better insight into the mechanisms of placebo and nocebo effects in pain and the possible benefits of conditioning compared to explicit expectation, future studies should carefully distinguish both methods of induction.
Gesehen am 29.07.2019